Using Google Ads to recruit and retain a cohort considering abortion in the United States - Ushma D. Upadhyay; Iris J. Jovel; Kevin D. McCuaig; Alice F. Cartwright (Elsevier, 2020)
Objective: The objective was to develop and test the feasibility of a methodology to recruit and retain individuals in the United States (US) who were considering abortion at the point of searching for an abortion clinic. Study design: We conducted the Google Ads Abortion Access Study, a national cohort study using a novel recruitment method - recruiting people searching for abortion care on Google. Advertisements for the study were displayed in search results. Users who clicked on the advertisement were directed to a landing page explaining the study and then to a screening form. Participants were eligible if they reported being pregnant and considering abortion. They completed an online baseline survey and 4 weeks later were invited by email or text message to complete a follow-up survey. Results: Over the course of 8 months, we recruited a racially/ethnically and geographically diverse cohort considering an abortion using Google Ads. After removing fraudulent cases, we recruited 1706 respondents, and among these, 1464 (86%) provided contact information for follow-up. Among those providing contact information, 1005 completed the follow-up survey, resulting in a 69% follow-up rate. Older age, white race, higher education, difficulty meeting basic needs, being not religious/spiritual and having no previous births were associated with higher follow-up. Total cost of the ads was $31.99 per completed baseline + follow-up survey. Conclusion: Researchers can use online advertising to successfully recruit populations early in their abortion-seeking process to understand the barriers they face and how to improve abortion access. Disadvantages include high cost and a small potential for fraudulent data. Implications: Google Ads is a feasible tool to recruit and follow a diverse sample of individuals who are considering abortion for studies investigating the barriers they face in obtaining a wanted abortion.